Is it possible that playing a video game might help you improve your computational thinking abilities? - Ceylan Zhao; Timothy Burgess (International Journal of Advanced Science and Computer Applications, 2022)
In this research, we looked at the cognitive and behavioral effects of playing Penguin Go, a video game that was created to help middle school kids improve their computational thinking (CT) abilities. Apart from the general efficacy of the game, we looked at the effects of a single game feature—constraints on the amount of blocks that may be used in a solution. Students' CT abilities increased dramatically after playing Penguin Go for fewer than two hours, according to the findings, but the extra limits had no meaningful effect on learning. Furthermore, although the game as a whole had no effect on students' views toward computer science, the limitations condition of the game had a detrimental effect on students' attitudes toward computer science. The outcomes of this study, as well as suggested possibilities for future research in the area of employing these sorts of games to build computational thinking abilities, are reviewed.